2016
DOI: 10.1016/j.ecoleng.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi (AMF) root colonization dynamics of Molinia caerulea (L.) Moench. in grasslands and post-industrial sites

Abstract: The aims of this studies were: (i) to examine the influence of heavy metal content (Zn, Cd, Pb, Fe, Cu) and other physico-chemical soil parameters on the level of root colonization of Molinia caerulea and (ii) to relate root colonisation parameters and soil variables to Molinia caerulea abundance in two contrasting habitats (grasslands and heavy metal contaminated sites).The sites differ significantly in terms of bio-available heavy metal contents, particularly Zn (34 times more than grasslands), soil texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The availability of HMs to microorganisms and higher plant species depends to a large extent on the soil properties and in particular on soil pH (e.g. Bąba et al 2016). As the alkalinity of soil increases, the mobility and thus bioavailability of HMs decreases due to increased precipitation and displacement from the sorption complex by alkaline ions e. g. Ca and Mg (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of HMs to microorganisms and higher plant species depends to a large extent on the soil properties and in particular on soil pH (e.g. Bąba et al 2016). As the alkalinity of soil increases, the mobility and thus bioavailability of HMs decreases due to increased precipitation and displacement from the sorption complex by alkaline ions e. g. Ca and Mg (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the presence, and abundance of the finest particle size fractions in soils are connected with the accumulation of some heavy metals (Zn, Pb, Cd), and can be responsible for the development of mycorrhiza in sites with strong metal stress (Cabała et al 2004;Bąba et al 2016). Studies on arbuscular mycorrhizal fungal root colonization dynamics of Molinia caerulea in grasslands and postindustrial sites have revealed that some of its mycorrhizal colonization parameters (mycorrhizal intensity, arbuscular richness) were negatively correlated with the clay and silt fractions in the soil and positively correlated with the percentage of sand fraction where higher species richness and diversity was recorded (Bąba et al 2016).…”
Section: The Relationship Between Vegetation and Soil Physicochemicalmentioning
confidence: 99%
“…All of which are the prerequisites for the establishment of permanent vegetation [67,[85][86][87][88].…”
Section: Industrial and Post-industrial Areas-ecosystem Service Potenmentioning
confidence: 99%